SPIRITUAL IMAGERY: FRAMING SPIRITUALITY IN MEN’S BODYCARE ADVERTISEMENTS - Hamani, Imara Al; Retnaningdyah, Pratiwi (J-ELLiT (Journal of English Language, Literature, and Teaching), 2023)
This article investigates the utilization of spiritual imagery in Kahf’s advertisement that continuously uses spiritual imagery in their advertisements. This article aims to reveal the utilization of spiritual imagery in advertisement that can attach and represent the brand’s identity to the audience. The authors gained the data by selecting textual and image components inside Kahf’s advertisements. The authors elaborating the findings using the theory of Popular Culture and connecting them to previous studies. This article focuses on discovering the use of spiritual imagery in framing spirituality in advertising to attach the audience. The result of this study shows that spiritual imagery such as the use of spiritual words, symbols, also the selection of images, and models in Kahf’s advertisements play important role in framing spirituality. The utilization of all of the spiritual imagery effectively leads Kahf’s advertisements to attach specific audiences and represent their brand’s identity.